Giant malignant phyllodes tumor of the breast: A rare case report and literature review - LIU, MIN (Oncol Lett, 2016)
Malignant phyllodes tumor of the breast (MPTB) is rarely encountered in clinical practice. Preoperative diagnosis is challenging due to nonspecific radiological and histological features, and the prognostic factors and optimal treatment remain controversial. The current report describes the case of a middle-aged female with giant MPTB who underwent multidisciplinary intervention, including surgery, postoperative chemotherapy and radiotherapy. To date, the disease-free survival (DFS) of the patient has reached 18 months. Furthermore, a related literature review summarize the clinicopathological characteristics and treatment progress regarding MPTB is presented, along with an analysis of the indications for therapeutic strategy in the current case. In the future, multi-center clinical trials must be initiated to identify the criteria for diagnosis and optimal treatment consensus for MPTB. In conclusion, the present case highlights that multidisciplinary management may contribute to DFS following the treatment of giant MPTB.